Reciprocal ST depression in acute myocardial infarction. - Odemuyiwa, O (1985)
ST segment depression in leads remote from those showing ST elevation during acute myocardial infarction has been attributed to benign electrical phenomena, distant myocardial ischaemia, or extensive myocardial damage. Eighty four consecutive survivors under 55 years of age with a first transmural myocardial infarction were studied. All patients had exercise tests six weeks after infarction and coronary angiography a mean of three months after infarction. Thirty eight (75%) of the 51 inferior and 19 (58%) of the 33 anterior infarcts showed reciprocal ST depression of greater than or equal to 1 mm during the acute phase. Ten (26%) of the 38 patients with inferior infarcts and reciprocal depression had ST depression in the same leads on exercise. There was concomitant disease of the left anterior descending artery in four (40%) of these 10 patients and in five (18%) of the 28 with inferior infarcts with reciprocal depression but without ST depression in the same leads on exercise. Five (26%) of the 19 patients with anterior infarcts with associated reciprocal depression and four of the 14 without reciprocal depression had important right coronary artery disease. In patients with inferior infarction important disease of the left anterior descending artery could not be predicted by ST depression in particular lead groups. Therefore reciprocal ST depression during acute myocardial infarction does not predict concomitant disease in the coronary artery supplying the reciprocal territory.